Hyperkalemic periodic paralysis : case report with a scna4 gene mutation and literature review (2020)
Hyperkalemic periodic paralysis is a rare musculoskeletal disorder characterized by episodic muscle weakness associated with hyperkalemia. It is a channelopathy associated with point mutations in the SCNA4 gene, with an autosomal dominant pattern of inheritance. We report the case of a 39-year-old patient with a picture with onset at six years of age, consisting of episodes of weakness caused by physical activity and intercurrent infectious processes, in whom a point mutation was found in the SCNA4 gene, not previously reported in the literature.